Roman Catholic Worship : Trent to Today, Second Edition - White, James F. (Book collections on Project MUSE., 2003)
"In this revised edition of Roman Catholic Worship, Professor White notes that contrary to often-expressed assumptions that nothing changed in Catholic worship from the Council of Trent to Vatican II, these four centuries witnessed significant change in devotions, church architecture and music, and in other ways than liturgical texts."--Jacket.